2020
DOI: 10.1111/jmcb.12697
|View full text |Cite
|
Sign up to set email alerts
|

Money, Bonds, and the Liquidity Trap

Abstract: This paper examines a search model of money and public bonds in which coordination frictions lead to multiple, Pareto ranked equilibria. Whether money and bonds are substitutes or complements, is not a primitive of the economy, but an equilibrium outcome. There exists an equilibrium resembling a liquidity trap, in which money and bonds are perfect substitutes, interest rates are zero, and monetary policy is ineffective; and a superior equilibrium in which money and bonds are complements, interest rates are pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The coexistence of alternative instruments with currency is a nontrivial topic in monetary theory, since the presence of other means of trade may drive domestic currency out of circulation. We have examined some of the issues involved in a closed economy setting, in Araujo and Ferraris (2019), where we found that, with public debt, if the agents can choose how to use the debt instrument, there is an equilibrium that resembles a liquidity trap, in which debt and money are used interchangeably to trade goods and debt carries no interest, and a Pareto superior equilibrium in which money is used to trade goods and interest bearing debt to reshuffle misallocated liquidity. Consider, for instance, the case of a one period public bond, issued at the beginning of every CM and sold for cash therein at a monetary price ρ1, and subsequently reimbursed one for one in money at the beginning of the following CM.…”
Section: Multiple Currenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The coexistence of alternative instruments with currency is a nontrivial topic in monetary theory, since the presence of other means of trade may drive domestic currency out of circulation. We have examined some of the issues involved in a closed economy setting, in Araujo and Ferraris (2019), where we found that, with public debt, if the agents can choose how to use the debt instrument, there is an equilibrium that resembles a liquidity trap, in which debt and money are used interchangeably to trade goods and debt carries no interest, and a Pareto superior equilibrium in which money is used to trade goods and interest bearing debt to reshuffle misallocated liquidity. Consider, for instance, the case of a one period public bond, issued at the beginning of every CM and sold for cash therein at a monetary price ρ1, and subsequently reimbursed one for one in money at the beginning of the following CM.…”
Section: Multiple Currenciesmentioning
confidence: 99%
“…One may naturally wonder whether these benefits would disappear, should other instruments, such as public debt, be available to reshuffle liquidity, and reward it with interest. In a closed economy version of this model, Araujo and Ferraris (2019) have shown that whether public debt can serve such a role turns out to be an endogenous outcome, as there is always a liquidity trap equilibrium in which debt pays no interest and does not help reshuffle misallocated currency. Thus, the benefit of having multiple currencies is more likely to manifest itself in environments in which money and bonds are close substitutes, as discussed further at the end of the paper.…”
mentioning
confidence: 99%